Desain Stiffener Ring pada Heavy Hydrocarbon Pressure Vessel terhadap Perubahan Tekanan - M. Novian Rizky N.P; Mohammad Miftachul Munir; Rizal Indrawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
Pressure vessel production process often experiences problems, one of problems is changing data sheet from customer, in this case pressure vessel is already in the fabrication process. Changes data sheet are found in external pressure which is 3.5 kg/cm2g from previous 1 kg/cm2g, then recalculation must be carried out refers to ASME BPVC Section VIII Division 1. Then stress analysis is carried out with FEM through Ansys software simulation to determine loading conditions on pressure vessel design. Then fatigue life analysis was carried out to determine value of usage factor. Calculation of new external design pressure, was found that MAEP condition in shell is 0.158 MPa, this value is less than external design pressure of 0.34 MPa. Calculation results show that pressure vessel must be installed with a stiffener ring. Two stiffener rings are designed circumferentially on the outside of shell. Then results of stress analysis show that highest stress value is located on head. This value is still below maximum allowable stress value for material head, which is 138 MPa and results of fatigue life analysis show that usage factor value is less than one, thus pressure vessel there is no fatigue failure during thespecified age.